2014
DOI: 10.3928/01477447-20141023-54
|View full text |Cite
|
Sign up to set email alerts
|

Hardware-Related Complications After Dorsal Plating for Displaced Distal Radius Fractures

Abstract: There has been a trend away from dorsal fixation of distal radius fractures secondary to a historically higher complication rate. However, the literature on low-profile dorsal plates and titanium implants for the treatment of these fractures is limited. The goal of the current study was to evaluate hardware-related complications and removal rates after open reduction and internal fixation of unstable, displaced distal radius fractures using a dorsal approach with a low-profile titanium plate. A single surgeon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 22 publications
1
15
0
1
Order By: Relevance
“…12 Recent improvements have made the locking plate thinner with a rounder edge, which has led to a lower complication rate. [7][8][9][10] In this study, we showed the excellent results of lowprofile DLP in both two types of fractures. The type 1 fracture causes dorsal shearing accompanied by compression force.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…12 Recent improvements have made the locking plate thinner with a rounder edge, which has led to a lower complication rate. [7][8][9][10] In this study, we showed the excellent results of lowprofile DLP in both two types of fractures. The type 1 fracture causes dorsal shearing accompanied by compression force.…”
Section: Discussionsupporting
confidence: 60%
“…3,5,6 However, a new generation of 1.0-to 1.6-mm, low-profile dorsal locking plates (DLPs) have been designed to minimize tendon irritation. [7][8][9][10] Here, we retrospectively reviewed on patients treated by DLPs. The purpose of this study was to demonstrate our surgical strategy and technique of DLPs for displaced distal radius fractures according to the fracture patterns.…”
mentioning
confidence: 99%
“…Our results are very similar to a recent study evaluating patients with distal radius fractures treated with titanium low-profile dorsal plates. 11 They reviewed 125 patients with displaced distal radius fractures treated with a low-profile titanium dorsal plating system. Though their follow-up period was only 1 year and most of our plates were volar while theirs were all dorsal, the percentage of patients requiring plate removal was 8% while we removed 11%.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the difficulty in removing the plates has been attributed to bony integration as well as mechanical binding between the titanium screw and plate. 10,11 Furthermore, the interaction between the plates and the overlying tendons has been implicated in a greater number of inflammatory responses and attrition ruptures. These have been compared in vivo to stainless-steel plates and found to be more problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Dorsal locking plates have the advantage of acting as a buttress to posterior comminution and the locking plates may also allow increased periosteal blood supply [ 38 ]. Dorsal plating fixation is an accepted treatment for unstable, dorsally displaced DRFs with many benefits, including the ease of exposure, visualization of the articular surface, and biomechanical advantage of plate placement as a dorsal buttress [ 39 ]. Previous studies showed that dorsal locking plating was associated with extensor tendon complications, consequently volar locking plating gained more acceptance.…”
Section: Discussionmentioning
confidence: 99%